Adaptation of Sharia Accounting in the Digital Economy: A Study of Sharia-Based Fintech Startups in Indonesia - Gina Puspita (Journal of Taxation Insights Policy Practice, 2025)
The digital transformation in the financial sector has spurred the emergence of Sharia fintech startups as an innovative alternative financial service that remains compliant with Sharia principles. However, the integration of digital financial systems and Sharia accounting still faces challenges, particularly in recording contract-based transactions and preparing financial reports in accordance with Sharia Financial Accounting Standards (PSAK). While previous studies have explored Sharia compliance in conventional financial institutions, research focusing on the contextual adaptation of Sharia accounting within the digital-based fintech ecosystem remains limited. This study addresses that gap by analyzing how Sharia fintech startups in Indonesia adapt Sharia accounting practices, identifying key challenges, and formulating a novel Digital Sharia Accounting Adaptation Model tailored for the digital economy. Using a qualitative case study approach involving three Sharia fintech startups, data were collected through in-depth interviews, questionnaires for certified employees, and direct observation of the financial information systems employed. Thematic analysis was conducted to identify patterns of adaptation and innovation in digital Sharia financial reporting. Findings reveal that adaptation is significantly influenced by technological readiness, understanding of Sharia accounting, and managerial support, while major obstacles include the absence of detailed regulatory guidelines and limited human resources. The proposed model integrates Sharia compliance, technology integration, and organizational readiness, providing a practical framework for developing robust, digital-based Sharia financial reporting systems in the era of financial technology.